2008
DOI: 10.3844/ajptsp.2008.14.18
|View full text |Cite
|
Sign up to set email alerts
|

Life Extension by Anti-Aging Drugs: Hormetic Explanation?

Abstract: A number of chemicals including antioxidants, vitamins and hormones are widely advertised as anti-aging drugs (geroprotectors). It is usually believed that life-extending capacity of geroprotectors may be attributed to their specific anti-aging mechanisms, even without solid scientific evidence. The analysis of the survival data gathered by both anti-aging and hormetic interventions demonstrates that many essential similarities exist between them. The evidence that life-extending effects of anti-aging drugs ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The intriguing relationship between aging and stress resistance is increasingly mentioned in contemporary gerontology [ 20 ]. Moreover, it was shown that many adaptogens have anti-aging properties; conversely, many anti-aging preparations were found to increase adaptive capabilities [ 21 ]. It has also been hypothesized that stressed plants can synthesize stress-signaling molecules, which increase stress resistance of herbivorous species [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intriguing relationship between aging and stress resistance is increasingly mentioned in contemporary gerontology [ 20 ]. Moreover, it was shown that many adaptogens have anti-aging properties; conversely, many anti-aging preparations were found to increase adaptive capabilities [ 21 ]. It has also been hypothesized that stressed plants can synthesize stress-signaling molecules, which increase stress resistance of herbivorous species [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In red-fleshed Dragon fruit, the most important antioxidant pigments are the betacyanins and betaxanthins (Wybraniec et al, 2001). Dragon fruit, as in many other fruits and vegetables, is also rich in antioxidants that help to reduce the incidence of degenerative diseases such as arthritis, arteriosclerosis, cancer, heart diseases, inflammation and brain dysfunction (Vaiserman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…With the higher number of hydroxyl groups, the tendency of chain breaking antioxidant behavior of the compound increases [20].Phenolic is found in abundant in plants which is the major secondary metabolites of plants, serving in plan defense mechanism for counteracting reactive oxygen species (ROS) [21,22].In cacti, red-violet betacyanin's and yellow betaxanthins are the most important fruit pigments, belonging to betalain pigments [23].Betalain is a class of water-soluble pigments that provide the colors in a wide ranging of flowers and fruits [24].Moreover, betacyanin's that are attached to n-heterocyclic compounds are a class of compounds that can also employed as antioxidants, with radical scavenging activities. Antioxidant activity of dragon fruit is mainly due to the content of ascorbic acid (vitamin C) [26].In living organisms, ascorbic acid serves in many physiological functions, such as acts reductant to prevent cellular components from oxidative damage [27].This is because ascorbic acid has the capability of serving as a scavenger in the oxidation of free radicals and oxygen-derived species, e.g., singlet oxygen, hydrogen peroxide and hydroxyl radicals [28].Hence, ascorbic acid is found to be very useful in the treatment of photo-aging [29].Instead, pro-oxidant properties of ascorbic acid also contribute to its antibacterial effects [30].In the human body, the formation of free radicals is regulated by various enzymes and antioxidants in response to exogenous stimuli. In the case of extensive production of free radicals, it could lead to traumatic injury, inflammation and other chronic events, such as cancer and degenerative disease, due to the oxidant stress [31].Over last few decades, few antioxidant vitamins which have the ability of limiting oxidative damage, have been introduced such as beta-carotene, vitamin C and vitamin E, thus minimizing the threats of particular chronic disease [32].This can be observed from the closely association of heart diseases and low plasma levels of beta-carotene, tocopherol and L-ascorbic acid in epidemiological studies [33].…”
Section: Phyto Chemical Composition Of Hylocere Usundatusmentioning
confidence: 99%